Philippine materials in international law - Pangalangan, Raul C. (Brill's Asian law series, 2022)
"This is a collection of international law materials relating to the Philippines: excerpts of treaties and declarations; international judicial and arbitral decisions; and Philippine constitutional clauses, statutes and Supreme Court decisions. Today new theories abound, calling for comparative perspectives that look at international law through the lens of national and regional practice. This book engages that challenge at a concrete level, e.g., how Marcos's human rights abuses were litigated abroad but never in Philippine courts, and how victim claims for reparations are, ironically, blocked by the Philippine Government citing the Filipino people's competing claims over Marcos's ill-gotten wealth. It retells Philippine history using international law, and re-examines international law using the Philippine experience"--